2004
DOI: 10.1016/s1386-1425(03)00340-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silver nano particles on the fluorescence quantum yield of Rhodamine 6G determined using dual beam thermal lens method

Abstract: Nano structured noble metals have very important applications in diverse fields as photovoltaics, catalysis, electronic and magnetic devices, etc. Here, we report the application of dual beam thermal lens technique for the determination of the effect of silver sol on the absolute fluorescence quantum yield (FQY) of the laser dye rhodamine 6G. A 532 nm radiation from a diode pumped solid state laser was used as the excitation source. It has been observed that the presence of silver sol decreases the fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…31 In contrary, a great enhancement is expected for Rh6G since a significant overlap exists between the luminescence absorption, emission and plasmonic absorption. 32,33 The Raman scattering and luminescence spectra recorded for probe molecules on the Ag nanopatterned array show surface enhancement of luminescence and Raman scattering. Studies were performed to assess the SERS reproducibility over the substrate by recording the Raman scattering spectrum over a number of points.…”
mentioning
confidence: 99%
“…31 In contrary, a great enhancement is expected for Rh6G since a significant overlap exists between the luminescence absorption, emission and plasmonic absorption. 32,33 The Raman scattering and luminescence spectra recorded for probe molecules on the Ag nanopatterned array show surface enhancement of luminescence and Raman scattering. Studies were performed to assess the SERS reproducibility over the substrate by recording the Raman scattering spectrum over a number of points.…”
mentioning
confidence: 99%
“…Gordon et al were the first to report the TL spectrometry (TLS) [9]. It has been used in a wide range of applications, such as: to measure very low optical absorption coefficients of transparent samples [10][11][12] (in solids and liquids), trace analyses, flowing streams, flow injection, determination of fluorescence quantum efficiency (in solids and liquids) [13][14][15][16][17], chemical reaction kinetics [18], mechanisms of losses in SSL materials [13,[19][20][21] and in dyes lasers [17], determination of phase transitions [22,23], characterization of thermo-optical properties at low and high temperatures [24,25], etc. There are very good review papers and books on the subject [18,23,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…It is also suggested that clustering of metal NPs can significantly affect the total heat generation and diffusion and vary the thermal diffusivity of CdSe-Au/ CdSe-Ag complexes. Most studies based on measurement of thermal diffusivity of metal nanofluids using TL studies 19,20,27,32,33 have reported enhancement of thermal diffusivity with metal nanoparticles in a dye colloidal system. Herein, we report the heat and charge transport mechanism of QD-metal nanohybrids which can be optimized using the properties of the QDs and metal.…”
Section: Resultsmentioning
confidence: 99%